Investigations of transmission dynamics of Nipah virus in Bangladesh - Abdul Malek; Nashidul Islam; Ashabul Hoque (Informatics in Medicine Unlocked, 2024)
This study has focused on the transmission dynamics of the Nipah Virus (NiV) and its controlling system. In this respect, we have developed a virus transmission model based on several compartments and discussed the model's basic reproduction number and stability analysis at disease-free equilibrium (DFE) and endemic equilibrium (EE) points. It is observed that the model is locally and globally asymptotically stable at DFE and EE for the basic reproduction number R0<1 and R0>1, respectively. We have also solved the model equations numerically using the Runge-Kutta (RK-45) method to investigate the effect of disease parameters. In the calculation, some parameter values are taken from several references. Lastly, the calculated results show that the infection rate of the exposed individuals highly influences the disease compartments. Furthermore, drug resistance is observed to be less effective than the treatment rate. In addition, it is found that the number of infected people is reducing with the increasing treatment rate.